Diferentes caminhos para formação docente: estratégias empregadas por coordenadores pedagógicos - Silva, Jeanny Meiry Sombra (2019)
In the context of discussions about professional teacher development, weekly pedagogical meetings at school have been identified as a privileged space for teacher training. In this context, the pedagogical coordinator plays the fundamental role of planning, organizing and conducting the meeting; enabling good learning situations among all. The interest in knowing and analyzing the formative proposals employed in the public meetings of public schools in São Paulo started this PhD research. The objective of this study is to identify which strategies of teacher training are being used by pedagogical coordinators in the collective meetings that occur weekly in the school and to analyze the conceptions of formation that guide the actions of these professionals. By strategy, we are based on the definition of Roldão: a global, intentional and organized conception of an action or set of actions with a view to achieving the purposes of targeted learning. The mixed methods were used as methodological procedures and allowed to combine quantitative and qualitative looks at the research, which were: survey, observation and narrative interview. The subjects were 380 pedagogical coordinators of Elementary and Middle School, professionals who act as teacher trainers in the schools of the metropolitan region of the state education network. The quantitative dimension questionnaire data were treated statistically as well as analyzed through Content Analysis. On the other hand, the qualitative dimension used the principles of French Speech Analysis as a procedure. The data were based on authors of the field of teacher education, among them: André, Almeida, Marcelo Garcia, Nóvoa, Pérez Gómez and Placco. The study pointed out that coordinators have different understandings of what training strategies are; among them some mentioned by them: thematization of the practice, case study, reading of theoretical texts, cultural outings, watching documentaries; and revealed that the selection and / or elaboration of training strategies is based to a large extent on implicit theories and idiosyncrasies, as well as on familiarities presumed with the craft and formations coming from SEE-SP central bodies rather than on an analysis accurate and shared understanding of the reality of concrete classroom situations and of the theoretical-methodological resources used by the teacher. The study also showed that in the discourses and in the actions of the coordinators, principles of both technical rationality and practical and critical rationality are present